The influence of problem-based learning model application on the improvement of student’s problem solving ability in learning mathematics - S Yulianti; I Parlina (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This study aims to determine the effect of Problem Based Learning model on student problem solving abilities in learning mathematics class X in SMA Bait Al-Quran. The study was conducted in the odd semester of the academic year 2017/2018. The type of research used is true experimental design with experimental design used in the form of random, pre-test, post-test design. The sample of this study was class X of Palestine as experimental class and class X of Yemen as control class. The learning process in the experimental class gets treatment with the PBL model and in the control class is taught by conventional learning model. Data collection using essay-type essay test technique is five questions to measure student problem solving abilities. Based on hypothesis test by using t-test at significant level (α) = 0,05. Based on the analysis of t-test the final test data is obtained value of Sig. (2-tailed) of 0.00 < 0.05 then according to the basis of decision-making in the T-Test can be concluded H0 rejected and Ha accepted. Thus the hypothesis proposed in this study proved, that there is a significant influence PBL model on the ability problem-solving mathematics students class X SMA Bait Al-Quran Kayuagung.